Recovery kinetics of dual AAV-mediated human otoferlin expression - Jonathan B. Sellon; Kathy S. So; Kathy S. So; Andrew D'Arcangelo; Sarah Cancelarich; Meghan C. Drummond; Peter G. Slade; Peter G. Slade; Ning Pan; Ning Pan; Tyler M. Gibson; Tian Yang; et al. (Frontiers in Molecular Neuroscience, 2024)
Deafness-causing deficiencies in otoferlin (OTOF) have been addressed preclinically using dual adeno-associated virus (AAV)-based approaches. However, timing of transduction, recombination of mRNA, and protein expression with dual hybrid AAV methods methods have not previously been characterized. Here, we have established an ex vivo assay to determine the kinetics of dual-AAV mediated expression of OTOF in hair cells of the mouse utricle. We utilized two different recombinant vectors that comprise DB-OTO, one containing the 5′ portion of OTOF under the control of the hair cell-specific Myo15 promoter, and the other the 3′ portion of OTOF. We explored specificity of the Myo15 promoter in hair cells of the mouse utricle, established dose response characteristics of DB-OTO ex vivo in an OTOF-deficient mouse model, and demonstrated tolerability of AAV1 in utricular hair cells. Furthermore, we established deviations from a one-to-one ratio of 5′ to 3′ vectors with little impact on recombined OTOF. Finally, we established a plateau in quantity of recombined OTOF mRNA and protein expression by 14 to 21 days ex vivo with comparable recovery timing to that in vivo model. These findings demonstrate the utility of an ex vivo model system for exploring expression kinetics and establish in vivo and ex vivo recovery timing of dual AAV-mediated OTOF expression.